2020
DOI: 10.1186/s12576-020-00753-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsin in mental health

Abstract: Neuropsin is a brain-expressed extracellular matrix serine protease that governs synaptic plasticity through activity-induced proteolytic cleavage of synaptic proteins. Its substrates comprise several molecules central to structural synaptic plasticity, and studies in rodents have documented its role in cognition and the behavioral and neurobiological response to stress. Intriguingly, differential usage of KLK8 (neuropsin gene) splice forms in the fetal and adult brain has only been reported in humans, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Previous studies have implicated KLK8 in the pathogenesis of several psychiatric disorders, including anxiety and depression [ 17 , 18 ]. In the present study, we first examined whether the depressive phenotypes of CUMS-exposed mice are associated with hippocampus KLK8 expression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have implicated KLK8 in the pathogenesis of several psychiatric disorders, including anxiety and depression [ 17 , 18 ]. In the present study, we first examined whether the depressive phenotypes of CUMS-exposed mice are associated with hippocampus KLK8 expression.…”
Section: Resultsmentioning
confidence: 99%
“…KLK8 (also known as neuropsin) is highly expressed in the hippocampus, amygdala, and other brain regions associated with emotion management, and plays a key role in neuroplasticity, learning, and memory processes [ 17 , 18 , 31 , 32 ]. Previous studies have suggested the relationship between KLK8 and behavioral regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropsin ( Klk8 ) is another gene affected in Setd1b cKO mice that plays a complex role in memory function. It regulates the extracellular matrix, leads to spatial reference memory impairment when deleted in mice (Tamura et al , 2006 ) and has been implicated with mental diseases (Bukowski et al , 2020 ) (Fig 3E ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, inactivation of KLK8 has protective effects against depressive-like behaviors and memory impairment initially induced by chronic stress in mice [ 23 , 26 ]. A more comprehensive review of the role of KLK8 in mental health phenotypes is available elsewhere [ 27 ].…”
Section: Introductionmentioning
confidence: 99%